Girlhood 2.0 the role of Instagram girl trends in Filipina Gen-Z's construction of girlhood - Cañamo, Frances Sydney L.
Amid the rise of globalized aesthetics and consumerist pressures on social media, this thesis examines how Instagram (IG) girl trends shape Filipina Gen-Z’s notions of girlhood by examining the portrayals they consume, their engagement with content, and how they make sense of these representations. Grounded in Harris’ (2004) dual narratives of modern girlhood, Jenkins’ (2006) participatory culture, reception theory, and critiques of consumerism, the study investigates the tensions between empowerment and commodification. Using a multi-method approach – textual analysis of IG content, a reception analysis of 10 in-depth interviews, and a creative workshop with 10 participants, the study reveals a gap between Instagram’s portrayals of girlhood and Filipina Gen-Zs’ lived realities. Participants navigate girlhood as fluid, conflicted, and shaped by both aesthetic desire and cultural dissonance. While critical of idealized, consumerist portrayals, they still engage with them cautiously and ambivalently, driven by aspiration and self-expression. Their participation reflects cultural dissonance, self-awareness, and a desire to redefine girlhood within a Western-dominated but personally meaningful digital space. The research calls for localized girlhood frameworks, creative methodologies, and mindful content creation that reflect Filipina girls’ emotional and social complexity.